THE INFLUENCE OF TRANSLATION STUDIES ON MODERN PHILOLOGICAL RESEARCH - Rasulova Diyora Ziyodulla qizi; Abduramanova Diana Valerevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Translation  studies has  become a transformative discipline,  crossing linguistic, cultural, and historical divides. This  article explores how  translation studies have reshaped modern philology, introducing interdisciplinary methodologies that enrich textual analysis and comparative research.  Examining case studies  of literary, historical, and sacred texts, this study highlights the integration of translation theories into philological practices, such as the analysis of meaning shifts, textual fidelity, and cultural mediation.  She argues that  translation studies not only  complement traditional philological  methods, but also  broaden the  scope of the field, fostering a more  comprehensive understanding of  world literatures and their  interrelated histories. This research  highlights the  need for translation as a tool and  as a  perspective for modern philological  research, opening the way  to innovative perspectives on  the transmission and  reception of texts.